Cascading effects of cyclones on the biodiversity of Southwest Pacific islands. (January 2016) - Goulding, W.; Moss, P.T.; McAlpine, C.A.
Abstract: Human induced climate change is having a dramatic impact on global biodiversity and insular assemblages are particularly vulnerable. However, the cascading impacts of tropical cyclones on insular ecosystems are poorly understood and expected to grow with the increasing intensity of these events associated with future anthropogenic climate change. This problem is particularly relevant to islands of the Southwest Pacific, which are cyclone-prone and support high levels of endemic biodiversity. In this perspective, we present new information from a case study of the indirect effects of a tropical cyclone (Ita) on forest extent and integrity from an endemic hotspot, the Louisiade Archipelago of Papua New Guinea. We highlight how a cyclone event can be a catalyst for human-coping strategies that increase pressures on forest ecosystems and expose them to invasive plant species. These changes represent a major threat to forest-dependent bird species, many of which are endemic. Rather than being an isolated example, these observations provide an insight into human responses to climate change over cyclone-prone tropical islands/regions where human populations are reliant upon subsistence agriculture and the resources provided by forests. The cumulative anthropogenic impacts on forest ecosystems are potentially catastrophic to the future of island biodiversity and greater than the long-term shifts in mean climate. Highlights: We examined the indirect impacts of a tropical cyclone upon island biodiversity. Cyclones are catalysts for human-coping strategies that increase pressure on forests. Cyclones alter the dynamics of invasive plant and animal species on islands. Impacts on island forests will threaten endemic and forest-dependent bird species. Increases in cyclone intensities will disproportionally threaten island biodiversity.